2013
DOI: 10.1242/jcs.122754
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of genomic imprinting by reprogramming and redifferentiation

Abstract: SummaryInduced pluripotent stem cells (iPSCs), generated from somatic cells by overexpression of transcription factors Oct4, Sox2, Klf4 and cMyc have the same characteristics as pluripotent embryonic stem cells (ESCs). iPSCs reprogrammed from differentiated cells undergo epigenetic modification during reprogramming, and ultimately acquire a similar epigenetic state to that of ESCs. In this study, these epigenetic changes were observed in reprogramming of uniparental parthenogenetic somatic cells. The parthenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Alteration of the uniparental imprinting status in Ndn was previously reported by Kim et al (2013), who found a loss of DNA methylation during induction of pluripotency in parthenogenetic NSCs. Ndn plays an important role in proliferation and apoptosis of NSCs and in neuronal development and terminally differentiated neurons.…”
Section: Derivation Of Nscs From Gps Cellssupporting
confidence: 60%
See 1 more Smart Citation
“…Alteration of the uniparental imprinting status in Ndn was previously reported by Kim et al (2013), who found a loss of DNA methylation during induction of pluripotency in parthenogenetic NSCs. Ndn plays an important role in proliferation and apoptosis of NSCs and in neuronal development and terminally differentiated neurons.…”
Section: Derivation Of Nscs From Gps Cellssupporting
confidence: 60%
“…S2). 8 Mest hypermethylation has been previously described in ESCs. 9 The aberrant methylation of imprinted genes like Mest in ESCs and ES-NSCs can be readily detected in human ESCs.…”
Section: Derivation Of Nscs From Gps Cellsmentioning
confidence: 99%
“…This fact is supported by the results of another study with iPSCs from neutral stem cells isolated from a partenogenetic mouse embryo. In these cells, the expression levels of the cells with paternal imprinting, Peg1 (or Mest ), Ndn and Snurf determined using microchips, was much lower than those in somatic cells from the embryos obtained by normal biparental fertilization, since these genes were reactivated during reprogramming [27]. Thus, the epigenetic memory phenomenon has a real impact on iPSC characteristics, and the consequences of its presence may be serious.…”
Section: Effect Of the Epigenetic Memory On The Properties Of Inducedmentioning
confidence: 99%
“…Among the various pluripotent cell types, iPSCs are the most similar to embryonic stem cells (ESCs), based on their molecular signature and differentiation potential, and they fulfill all the criteria for pluripotency -the formation of germline-competent chimeras (Okita et al, 2007), germline transmission (Kim et al, 2008;Shi et al, 2008) and full-term development after tetraploid complementation (Kang et al, 2009;Zhao et al, 2009). The generation of iPSCs also entails epigenetic modification, such as changes in genomic imprinting (Kim et al, 2013), histone modification (Maherali et al, 2007) and reactivation of the inactive X chromosome (Xi) (Maherali et al, 2007;Ohhata and Wutz, 2013). Generally, the efficiency of iPSC derivation using four transcription factors varies depending on the origin of the somatic cells, and ranges from 0.01 to 3.6% (Takahashi and Yamanaka, 2006;Maherali et al, 2007;Okita et al, 2007;Wernig et al, 2007;Huangfu et al, 2008;Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%